Elaboração de um modelo epistemológico de referência e de uma proposta de ensino para os inteiros relativos influenciado por um grupo de estudos com professores. - KLEBER RAMOS GONÇALVES (2022)
This research answered the following generatrix question: What teaching proposal for Z can be built through interaction with a group of teachers from a PQM perspective? To do so, we built an Epistemological Model of Reference that allowed us to analyze the Dominant Model of the content in question. The theoretical reference mobilized was the Anthropological Theory of the Didactic, more specifically aspects of the Paradigm of Questioning the World. We also mobilize conditions and restrictions identified from the conclusions of a continuing education with the group of teachers of mathematics laboratories of the Municipal Teaching Network of Campo Grande/MS, developed with principles of the Paradigm of Questioning the World. These conclusions also allowed us to complement the Epistemological Model of Reference. This work was also based on studies about the of Study and Research Course analyzed through the dialectics, Question/Answers, Media/Milieu and Collective/Individual. Thus, coherently, we present the text of the thesis in the format of a question and answer map, in which two heart answers are presented, one answer referring to the study group and the other to the thesis. The analyses performed evidenced, among other aspects, a teaching based on concrete models, whose technological-theoretical block is given by didactic creations. In this sense, the activities of the alternative proposal were based on a teaching given by the entrance of relative integers via studies of school algebra combined with concrete models, particularly in the properties that justify the techniques for these numbers, as well as the mobilization of various contexts so that these numbers are understood beyond the idea of measure.